The proceedings of the coastal sediments 2015 - Wang, Ping; Rosati, Julie Dean; Cheng, Jun (Geologist) (World Scientific Publishing Company, 2015)
"This Proceedings contains over 260 papers on cutting-edge research presented at the eighth international Symposium on Coastal Sediment Processes, held May 11 - 15, 2015, in San Diego, California, USA. This technical specialty conference was devoted to promoting an interdisciplinary exchange of state-of-the-art knowledge among researchers in the fields of coastal engineering, geology, oceanography, and related disciplines, with the theme of Understanding and Working with Nature. Focusing on the physical aspects of the sediment processes in various coastal environments, this Proceedings provides findings from the latest research and newest engineering applications. Sessions covered a wide range of topics including barrier islands, beaches, climate and sea level, cohesive and noncohesive sediments, coastal bluffs, coastal marsh, dredged sediments, inlet and navigation channels, regional sediment management, river deltas, shore protection, tsunamis, and vegetation-sediment interaction. Several special sessions included: Relevant science for changing coastlines: A Tribute to Gary Griggs; North Atlantic Coast Comprehensive Study and post-super-storm Sandy work; long-term coastal evolution; barrier islands of Louisiana; sea-level rise and super storms in a warming world; predicting decadal coastal geomorphic evolution; and contrasting Pacific coastal behavior with El Niño Southern Oscillation (ENSO), are also featured."--